2017
DOI: 10.1001/jamaophthalmol.2017.3398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation With Lutein, Zeaxanthin, and ω-3 on Macular Pigment

Abstract: IMPORTANCE Nutritional uptake of lutein, zeaxanthin, and ω-3 polyunsaturated fatty acids may increase macular pigment optical density (MPOD) and thereby protect against the development of age-related macular degeneration (AMD).OBJECTIVES To estimate the efficiency of dietary supplementation containing lutein, zeaxanthin, ω-3 polyunsaturated fatty acids, and vitamins to increase the density of macular pigment in first-generation offspring of parents with neovascular AMD. DESIGN, SETTING, AND PARTICIPANTSThis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…In recent studies, particular emphasis has been placed on the role of ω3 PUFAs in eye diseases. The positive effect of ω3 treatment was investigated in animal models of retinal and optic nerve pathologies45 47 48 52 and in clinical studies of AMD and dry eyes 57–59. Although the results were not conclusive, we investigated the effect of ω3 PUFAs in age-associated retinal degeneration in healthy mice.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, particular emphasis has been placed on the role of ω3 PUFAs in eye diseases. The positive effect of ω3 treatment was investigated in animal models of retinal and optic nerve pathologies45 47 48 52 and in clinical studies of AMD and dry eyes 57–59. Although the results were not conclusive, we investigated the effect of ω3 PUFAs in age-associated retinal degeneration in healthy mice.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed time course of XP repletion in two volunteers has shown a steady increase for 140 days after initiation of supplementation, followed by a plateau or slight decrease to 1 year or more 157. Many studies report that dietary supplementation results in higher MPOD (measured behaviorally or via several imaging technologies) at the earliest time points tested, typically 2 to 4 months and depending on the dose and baseline XP levels in test subjects 131,158169. XP removal is less well documented, with limited data suggesting stable, slightly decreasing, or baseline MPOD 157,169.…”
Section: Considering Dietary Delivery Of Xanthophyll Pigmentmentioning
confidence: 99%
“…In the Western countries, the relationship with macular pigment density and circulating levels of DHA and EPA has been studied [30]. Limpia study recently found an association between increased macular pigment optical density (MPOD) with circulating levels of omega-3 docosapentaenoic acid as well [31], but nutrient supplementation did not change the MPOD [32].…”
Section: Discussionmentioning
confidence: 99%